PERTANGGUNGJAWABAN PIDANA TERHADAP GELANDANGAN DAN PENGEMIS (GEPENG) DITINJAU DARI PERSPEKTIF HAM (STUDI KASUS PENGADILAN NEGERI SINGARAJA) - Adi Prasetya Atmaja, Ketut; Yusa Darmadi, A.A. Ngurah; Walesa Putra, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Vagrants and beggars or often called gepeng is a classic problems that must beaddressed by the government in order to maintain public order. The one way thegovernment act is the regulation of Buleleng regency with Buleleng Local RegulationNo. 6 Year 2009 regarding Public Order containing provisions to criminalize thegepeng. Meanwhile gepeng is part of the poor people that must be protected andpreserved as they have human rights set forth in the Constitution of Republik ofIndonesia Year 1945.
Keywords: Criminal Responsibility, Gepeng, Human Rights, Buleleng Regency